PREDICTING THE DEVELOPMENT OF PREECLAMPSIA BASED ON CLINICAL AND GENETIC FACTORS: A REVIEW - Radjabova Zulola Abdukhakimovna (Web of Journals Publishing, 2023)
Preeclampsia (PE) is a multifactorial complication of pregnancy that poses a serious threat to both mother and fetus, requiring accurate prediction for timely prevention. This review analyzes current data on clinical and genetic predictors of PE, with a focus on the role of the renin-angiotensin system (RAS) and, specifically, the AGTR1 and AGTR2 genes. Key pathogenetic mechanisms are examined, including endothelial dysfunction, oxidative stress, trophoblast apoptosis, and immune maladaptation. Clinical risk factors (age, medical history, comorbidities) and their interaction with genetic predictors are analyzed. The principles of developing and validating multifactorial predictive models, which demonstrate high sensitivity (up to 89.5%) and specificity (up to 84.6%), are described. Practical aspects of genotyping, preventive strategies (aspirin, risk factor modification), and promising research directions (GWAS, epigenetics, biomarkers) are discussed. The importance of a personalized approach to pregnancy management to improve perinatal outcomes is emphasized.